PERBANDINGAN TINGKAT KESEHATAN BANK SYARIAH SEBELUM DAN SETELAH GO PUBLIC (Studi Pada PT. Bank Panin Dubai Syariah Tbk) - Desi Annisa; Isfandayani - (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2020)
Go public is one way for companies to take funding sources outside the company. This funding source is expected to provide facilities for companies to expand and have a good impact on company performance. This study aims to examine how the health level of Islamic banks after go public when compared with before go public. The method used in this study is to use a different test. Before a different test is performed first, the Shapiro-Wilk Normality Test, data that is normally distributed using the Paired Sample T-Test with α = 5%. namely NPF and CAR, while data that are not distributed use the Wilcoxon Test α = 5%, namely ROA and NOM. The results of the study show NPF, NOM, and CAR get a value of α <5% which means there are differences in the level of health of Islamic banks before and after go public and ROA get values> 5% which means there is no difference in the level of health of Islamic banks before and after go public.